1997
DOI: 10.1086/310949
|View full text |Cite
|
Sign up to set email alerts
|

A Measurement of the Density Parameter Derived from the Evolution of Cluster X-Ray Temperatures

Abstract: We have, for the first time, determined the cluster X-ray temperature function at a redshift other than zero. The observed evolution of the temperatures is mild to a redshift of one-third. The normalization of the luminositytemperature relation is 0.92 ‫ע‬ 0.07 of the low-redshift relation (1 j error), assuming that its shape is the same. Such behavior occurs when clusters form with constant central entropy. The evolution of the temperature function implies that Q 0 is 0.50 ‫ע‬ 0.14 assuming an open universe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
175
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(192 citation statements)
references
References 46 publications
(47 reference statements)
14
175
3
Order By: Relevance
“…They provided the first line of evidence for the existence of dark matter (Zwicky, 1933;Smith, 1936), and cluster mass-to-light ratio measurements suggested that the matter density in the universe was sub-critical (Ω m < 1) as far back as the early 1970's (see Gott et al, 1974, and references therein). The evidence for low Ω m was substantially strengthened by baryon fraction measurements Evrard, 1997), and by the discovery of massive clusters at high (z ≈ 0.8) redshift (e.g., Henry, 1997;Eke et al, 1998;Donahue et al, 1998). Today, clusters remain an important cosmological tool, capable of testing cosmology in a variety of ways.…”
Section: General Principlesmentioning
confidence: 99%
“…They provided the first line of evidence for the existence of dark matter (Zwicky, 1933;Smith, 1936), and cluster mass-to-light ratio measurements suggested that the matter density in the universe was sub-critical (Ω m < 1) as far back as the early 1970's (see Gott et al, 1974, and references therein). The evidence for low Ω m was substantially strengthened by baryon fraction measurements Evrard, 1997), and by the discovery of massive clusters at high (z ≈ 0.8) redshift (e.g., Henry, 1997;Eke et al, 1998;Donahue et al, 1998). Today, clusters remain an important cosmological tool, capable of testing cosmology in a variety of ways.…”
Section: General Principlesmentioning
confidence: 99%
“…The Einstein Medium-Sensitivity Survey (EMSS) has the largest areal coverage of any of these (734 deg2 above a 0.3È3.5 keV Ñux limit of 3.57 ] 10~12 ergs s~1 cm~2, falling to 40 deg2 above 1.33 ] 10~13 ergs s~1 cm~2) yielding a total of 104 clusters (Gioia et al 1990 ;Henry et al 1992). The measurement of temperatures for several of these clusters with redshifts above 0.3 (e.g., Henry 1997) Vol. 547…”
Section: Cluster Surveysmentioning
confidence: 99%
“…A great deal of attention (Henry 1997 ;Bahcall & Fan 1998 ;Eke et al 1998 ;Sadat, Blanchard, & Oukbir 1998 ;Borgani et al 1999 ;Reichart et al 1999b ;Viana & Liddle 1999 ;Blanchard et al 2000) has been paid to this issue in recent years. To date, no consensus as to the value of has ) 0 been reached, due, in large part, to the inadequacies of the cluster catalogs currently available.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of recent studies have shown that clusters of galaxies suffer from little evolution, and their dynamical properties have remained almost unchanged since z ∼ 0.8 (Mushotzky, & Scharf 1977;Bahcall, Fan, & Cen 1997;Henry 1997;Rosati et al 1998;Vikhlinin et al 1988;etc.). This essentially justifies the employment of the Jeans equation for X-ray emitting gas in the lensing clusters at intermediate redshifts.…”
Section: Strong Lensing: Overestimates Cluster Mass ?mentioning
confidence: 99%